Sertifikasi Halal Mempengaruhi Peningkatan Daya Saing UMKM di Jakarta - Fajar Julian Azhari; Novianti Rachmayani; Irwan Aufi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of the mandatory halal certification policy on improving the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the Jakarta area. This study was conducted using a qualitative approach through a literature review of various scientific publications relevant to the topic. The scope of the study includes regulatory aspects related to halal certification, the level of readiness of MSMEs to meet the established requirements, and its impact on market accessibility and consumer trust. The findings of this study indicate that the implementation of mandatory halal certification has positively contributed to strengthening product image, expanding the market, and increasing the added value of MSME products, particularly those operating in the food, beverage, and cosmetics sectors. Halal certification not only provides assurance for Muslim consumers but can also be attractive to international markets that require similar standards. This indirectly encourages MSMEs to improve the quality of their production and business governance. However, the implementation of this policy still faces several obstacles. Some MSMEs do not yet understand the urgency and benefits of halal certification. Furthermore, the lack of tangible consequences for businesses that have not yet obtained certification leads to low compliance. High certification costs and complicated administrative procedures are also major obstacles, particularly for MSMEs with limited resources. Based on the analysis, it can be concluded that the mandatory halal certification policy has significant potential to boost MSME competitiveness, all supported by a sustainable training strategy, adequate technical assistance, digitalization of the certification process, and affirmative action policies that favor the small and micro business sector. Therefore, synergy between the government, certification bodies, and MSMEs is key to optimizing the implementation of this policy.